Optimalisasi Pengelolaan Sampah dan Kebersihan Lingkungan Melalui Pemberdayaan Masyarakat di Desa Buni Bakti - Maidani Maidani; Ilham Cahya Nugraha; Fadhel Muhammad; Siti Zulfah; Melli Wahyu Ningsih; Alika Dindania Sahari; Gilang Nurfalah; Yotam Erwin Rommel Tauk; Claudia Putri Setiadi; Pulung Rizki Utama; Amelia Lusiana Briliana; Valentino Quraish Lazuardi; Nadiah Famay Zarotin; Saiwaa Ghynaa Dhya Syifa Putri Ning Teguh; Alfira Kirana Sekarwangi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Environmental cleanliness and suboptimal waste management are still real challenges in rural areas, which have a direct impact on public health and productivity in the agricultural sector. The community service program through KKN Group 49 in Buni Bakti Village, Babelan District, Bekasi Regency, was carried out with the aim of optimizing waste management and environmental cleanliness through participatory community empowerment. The implementation method includes situation analysis, active involvement of residents, and the execution of work programs structured in four core pillars, namely: cleaning irrigation canals, construction of garbage bin facilities at SDN Buni Bakti 02, interactive socialization of waste sorting, as well as the installation of environmental education information boards and legal information assistance. The results of the activity show that there is an increase in the smooth flow of water in the irrigation system, the availability of more adequate hygiene infrastructure, and an increase in ecological awareness of residents and elementary school students. Empowering local elements has proven to be the main strategy in encouraging the transformation of collective behavior towards the sustainability of the village environment. This program emphasizes that waste management based on community participation can be an effective intervention model to improve the quality of life while supporting the sustainability of the agricultural sector in rural areas.